PENGARUH PEMBELAJARAN PAI TERHADAP PEMBENTUKAN AKHLAK SISWA KELAS XII DI SMAN 1 TEGALWARU - Anggita Lestari; Iqbal Amar Muzakki; Afiyatun Kholifah (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2026)
In the context of modern education, Islamic Religious Education (PAI) is an important tool for fostering the development of morals and character of students as a whole. This study aims to determine the influence of Islamic Religious Education (PAI) teaching on the moral growth of grade XII students of SMAN 1 Tegalwaru. The background of this study is the importance of the role of PAI in fostering moral and spiritual values ​​of students at the senior high school level, especially in dealing with moral difficulties experienced by students. The approach used is quantitative, and data were collected through a closed questionnaire compiled using indicators of PAI learning variables and student morality. The Spearman Rank correlation test was used to evaluate the results of the analysis showed a strong correlation between student moral development and Islamic Religious Education learning, with a significance level of 0.000 (p <0.05) and a correlation coefficient of 0.753. This shows the great influence of understanding Islamic Religious Education on student values. This study emphasizes the importance of maximizing Islamic Religious Education learning through the use of application-based, contextual, and exemplary methods.